A Vertical Asymmetry in Saccades (Journal of Eye Movement Research, 2015)
Visual exploration of natural scenes imposes demands that differ between the upper and the lower visual hemifield. Yet little is known about how ocular motor performance is affected by the location of visual stimuli or the direction of a behavioural response. We compared saccadic latencies between upper and lower hemifield in a variety of conditions, including short-latency prosaccades, long-latency prosaccades, antisaccades, memory-guided saccades and saccades with increased attentional and selection demand. All saccade types, except memory guided saccades, had shorter latencies when saccades were directed towards the upper field as compared to downward saccades (p